A documentação pedagógica na educação infantil e o desenvolvimento profissional docente - Hartmann, Anelise Auler (2022)
The advances that Early Childhood Education has achieved in recent decades are undeniable, especially visible in the conceptions and guidelines present in the policy documents for this stage of Basic Education. Among these advances, there is the recognition of the child as a social subject with rights, who must be the protagonist of his development, in dialogue with his peers, with adults and with the environment. The school is, for excellence, a space for socialization where subjects interact dialogically and are inserted in the forms of culture, central stage for the child to be the protagonist of his learning processes and to constitute themselves socially. In this direction, the research investigated the relationship between pedagogical documentation, reflection and teacher qualification in Early Childhood Education, based on the question: What are the possibilities for the practice of pedagogical documentation to be used as a strategy for reflection and teacher professional development? The dissertation adopted as a general objective to investigate what the relationship and the point of convergence between pedagogical documentation and teacher professional development is. As a methodological procedure, a qualitative research was carried out, supported by a bibliographic and documental review. The dissertation is divided into three main chapters (in addition to the initial and final considerations). In the first one, the content of the pedagogical documentation proposal founded by Loris Malaguzzi is discussed. In it, its uses, conceptions and guidelines are discussed, such as teaching and learning through relationships, the concept of one hundred languages for children and the integration of pedagogical documentation through the processes of observation, recording and reflection. Then, in the second chapter, we start from the recognition of the current legislation in Brazil, on the field of Early Childhood Education, presenting the historical course of the establishment of Early Childhood Education in Brazil, as a level of education and children's rights. The investigation was based on the conception of the child as a person, subject of rights and producer of culture, and of childhood as a social category, supported by the thinking of Barbosa (2006), Oliveira (2011), among others. The teacher training policy is emphasized through current legislation and curricular documents that guide national education. Finally, in the third chapter, the concept of reflective teacher is analyzed from the perspective of Freire (1968, 1996), Schön (1998), Zeichner (1993, 2008) and Contreras (1999), who in their research defended and emphasized the importance of the professional who reflects on their actions. Continuing, an analysis of the concept of teacher professional development was carried out in dialogue with the pedagogical documentation specifically emphasized by the teacher's reflection on his own practice, in a reflective and dialectical process. Based on these data, we sought to situate the pedagogical documentation as a teaching activity that narrows the dialogue between theory and practice, in order to enable a more conscious, intentional and reflective attitude in relation to teaching practice. Such an attitude helps to create conditions for the maximum development of human qualities in children and an opportunity for professional teacher development. This analysis, it is hoped, extends to Early Childhood Education the possibility of questioning assumptions naturalized in pedagogical practice, expanding possibilities of thinking about the qualification conditions of Early Childhood Education professionals.